2023
DOI: 10.3390/f14050985
|View full text |Cite
|
Sign up to set email alerts
|

A Re-Inventory after 12 Years—Increase in Red Wood Ant Nests and Woodpecker Cavities in Nests in the West Eifel Volcanic Field despite Climatic Changes

Abstract: We re-inventoried red wood ant nests (RWA) in 12 study sites (≈1281 ha) in the tectonically active Westeifel Volcanic Field, Germany, in an area-wide and integrated ecosystem approach after 12 years. Combined with the re-identification of previously mapped nests using a photo database, this approach leads to more accurate nest counts in (re)inventories. A total increase in nests from 1144 (2009) to 1252 (2021), and a dramatic one for the Heidberg site by 52-fold (2009) and 85-fold (2021) compared to a 1984 inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
22
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(34 citation statements)
references
References 33 publications
11
22
1
Order By: Relevance
“…In the Oberpfalz, the preferred tree age classes by RWA nests correspond to the averaged tree age: medium mature (61-80 years) and mature (≥81-140 years) pine-dominated forests (Figure 3), confirming our findings of previous inventories [7] in both the Oberpfalz and the WEVF [32] that F. polyctena and all nest heights are more abundant in mature forests. Mature spruce-dominated forests are habitats for start-ups, short and medium-sized nests, but with lower proportions compared to pine forests.…”
Section: Tree Species and Agesupporting
confidence: 87%
See 4 more Smart Citations
“…In the Oberpfalz, the preferred tree age classes by RWA nests correspond to the averaged tree age: medium mature (61-80 years) and mature (≥81-140 years) pine-dominated forests (Figure 3), confirming our findings of previous inventories [7] in both the Oberpfalz and the WEVF [32] that F. polyctena and all nest heights are more abundant in mature forests. Mature spruce-dominated forests are habitats for start-ups, short and medium-sized nests, but with lower proportions compared to pine forests.…”
Section: Tree Species and Agesupporting
confidence: 87%
“…This study clearly showed that the total number of active RWA nests increased by ≈8 % at both sites, but also for BSF (≈5 %), MF (≈36 %) and PF (≈93 %; Tables 1 and 2). These findings are confirmed by a comparable 12year re-inventory in the West Eifel Volcanic Field (WEVF), which also showed an overall increase in RWA nests (≈10%) and an increase in active nests by ≈6 % [32].…”
Section: Presence/absence Data Of Rwa Nestssupporting
confidence: 62%
See 3 more Smart Citations